ANALISIS MEKANISME DAN PENERAPAN PENGELOLAAN DANA PENSIUN SYARIAH TERHADAP FATWA DSN-MUI NOMOR 88/DSN-MUI/XI/2013 PADA BANK SYARIAH CABANG TAMALANREA - Nuhung, Mahmud; Hidayat, Hidayat (Jurnal Ar-Ribh, 2020)
This study aims to determine the Mechanism and Implementation of Shariah Pension Fund management regarding the MUI DSN Fatwa Number 88/DSN-MUI/XI/2013 in Bank Syariah Mandiri. This research is a case study research with a qualitative descriptive approach. The Sharia Pension Fund Management Mechanism at Bank Syariah Mandiri is manageable, which starts with salary transfer by Bank Syariah Mandiri to PT TASPEN, then the Customer can choose Sharia Pension Fund Services at Bank Syariah Mandiri with the choices of Payroll Partners using the Mudharabah Muthlaqah Agreement or Financing using the Murabahah Agreement or Ijarah Agreement. The Application of Sharia Pension Fund Management satisfies the Fatwa of MUI DSN Number 88 / DSN-MUI / XI / 2013 unless at the Term of PT TASPEN and Customer.